Transportation to primary percutaneous coronary intervention, compared with on-site fibrinolysis, is a strong independent predictor of functional status after myocardial infarction: 5-year follow-up of the PRAGUE-2 trial. Issue 2 (1st June 2014) - Mocova Bilkova, Dana; Motovska, Zuzana; Prochazka, Bohumir; Groch, Ladislav; Zelizko, Michael; Aschermann, Michael; Widimsky, Petr; ,
Abstract: Aims: Subjective symptoms represent significant criteria of a patient's health condition; therefore, we focused on the long-term prevalence of heart failure symptoms and angina pectoris after myocardial infarction between two groups of patients in which two different therapeutic strategies were used during the acute phase of ST-elevation myocardial infarction (STEMI). Methods: The PRAGUE-2 study enrolled 850 patients with STEMI. The patients were randomized into two groups – transport to a primary percutaneous coronary intervention (PCI) centre ( n =429) vs. fibrinolysis in community hospitals ( n =421). The data were collected from either primary hospitals or PCI centres, as well as via questionnaires. Results: The mean follow-up was 58 months. At 5 years, 45.4% of patients were in New York Heart Association class I following primary PCI vs. 31.8% of those treated with fibrinolysis (OR 2.02, 95% CI 1.37–2.97, p <0.002). At 5 years, 83.6% of patients had no symptoms of angina pectoris following invasive therapy vs. 58% of patients treated with fibrinolysis (OR 4.47, 95% CI 2.79–7.18, p <0.001). Conclusions: The symptoms of angina pectoris and heart failure were significantly lower in patients assigned to primary PCI in the acute stage of myocardial infarction compared with patients treated with fibrinolysis at the 5-year follow up.